The action of therapeutic ultrasound on the catalytic activity of the dissociating enzymes - ROZANOVA, N. A.; CHETVERIKOWA, E. P. (Archives of Acoustics, 1984)
The action of low intensity therapeutic ultrasound (0.88 MHz; 0.05 – 1.0 W/cm^2) on the activity and dissociation of the enzymes with labile quarternary structure was investigated (creatine kinase – CS, pyruvate kinase – PK, hexokinase HK and urease). It was shown that ultrasound does not affect the activity of these enzymes in solution. Dissociation of CR was activated by ultrasound when equilibrium forms in solution were not reached. Activation of the rate of the catalytic reaction in the case of immobilized HS was also obtained. This effect may consist in enhancement of the reaction product transport from the bottom of the experimental cell up to where the aliquote volume was replaced for measuring.